PERANCANCANGAN SISTEM INFORMASI DATA INVENTARIS BARANG PADA DINAS KESEHATAN KABUPATEN MUARO JAMBI - Elzas -; Eko Irwansyah (JURNAL AKADEMIKA)
Information system of stuff inventory data in the Muaro Jambi Department of Health now has to use a computerized system simply using Microsoft Office so that the generated data are less effective and efficient. So it is necessary to apply an information system design with Visual Basic 6.0 programming in stuff inventory processing dataat the Muaro Jambi Department of Health. With the new data processing system which is expected to overcome the constraints that exist on the old system.